Methods of Teaching Physics Interactive Methods - Ramazonovich, Kamolov Ikhtiyor; Dilshodovna, Ravshanova Saodat (European Journal of Life Safety and Stability (2660-9630), 2021)
This article discusses the technique of teaching physics using interactive methods. The main components of interactive lessons are interactive exercises and assignments that are completed by students.